A Note on the Triple Laplace Transform and Its Applications to Some Kind of Third-Order Differential Equation - Abdon Atangana (Abstract and Applied Analysis)
We introduced a relatively new operator called the triple Laplace transform. We presented some properties and theorems about the relatively new operator. We examine the triple Laplace transform of some function of three variables. We make use of the operator to solve some kind of third-order differential equation called “Mboctara equations.”